2010
DOI: 10.1016/j.plefa.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin and quercetin are naturally occurring co-substrates of cyclooxygenases in vivo

Abstract: Bioflavonoids are ubiquitously present in the plant kingdom, and some of them are presently being sold as healthy dietary supplements around the world. Recently, it was shown that some of the dietary polyphenols were strong stimulators of the catalytic activity of cyclooxygenase I and II, resulting in increased formation of certain prostaglandin (PG) products in vitro and also in intact cells in culture. In the present study, we investigated the effect of two representative dietary compounds, quercetin and myr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…In earlier studies [ 21 , 22 ], we showed, for the first time, that some natural phenolics, such as quercetin and myricetin, can serve as reducing cosubstrates of COX-1 and COX-2 and activate their catalytic activity. This phenomenon was confirmed in an in vitro cell culture model [ 21 ] and an in vivo animal model [ 23 ]. Notably, these compounds are effective in activating the COX enzymes in cultured cells with effective concentrations in the nM range [ 21 ].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In earlier studies [ 21 , 22 ], we showed, for the first time, that some natural phenolics, such as quercetin and myricetin, can serve as reducing cosubstrates of COX-1 and COX-2 and activate their catalytic activity. This phenomenon was confirmed in an in vitro cell culture model [ 21 ] and an in vivo animal model [ 23 ]. Notably, these compounds are effective in activating the COX enzymes in cultured cells with effective concentrations in the nM range [ 21 ].…”
Section: Introductionmentioning
confidence: 75%
“…It is suggested that ethyl gallate exerts this effect through the activation of the peroxidase active site of COX-1 and COX-2 by serving as a reducing cosubstrate for P + Fe IV , in a similar manner as quercetin (reported in [ 21 , 22 , 23 , 24 ]). This suggestion is based on the following observations: (i) The activating effect of ethyl gallate on PGE 2 production in vitro and in vivo reported in this study closely mirrors the activating effect of quercetin reported earlier [ 21 , 23 ]. (ii) Activation of PGE 2 production by ethyl gallate can be inhibited in a concentration-dependent manner by galangin, and a mirroring inhibitory effect of galangin was also observed recently with quercetin [ 29 ].…”
Section: Discussionmentioning
confidence: 94%
“…in single i.v. injection [31]. At lower doses up to 0.3 mg/kg QER stimulated the formation of PGE2 by about 5-fold.…”
Section: Phytoestrogensmentioning
confidence: 85%
“…However, the activities of SOD and GSH-Px were significantly increased by myricetin. By acting as a co-substrate for the cyclo-oxygenases, the compound stimulated the formation of prostaglandin products in Sprague-Dawley rats [ 133 ]. It was observed that myricetin doses below 0.3 mg/kg b.w.…”
Section: Pharmacological Applicationsmentioning
confidence: 99%